2008
DOI: 10.1016/j.juro.2007.11.049
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Approach Toward Novel Serum Biomarkers for Benign Prostatic Hyperplasia: The MPSA Consortium

Abstract: Purpose-Clinical benign prostatic hyperplasia (BPH) is primarily diagnosed based on a diverse array of progressive lower urinary tract symptoms (LUTS) and is likely distinct from histological BPH, which is detected by the presence of non-malignant proliferation of prostate cells but may or may not be associated with symptoms. Pharmacological management of LUTS has emerged as an effective initial treatment for clinical BPH due to the introduction of new drug therapies shown to be effective in recent large clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Recognizing the importance of targeted therapies for management of BPH, the National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) established the MTOPS Prostatic Samples Analysis (MPSA) Consortium in 2002 to “identify and validate molecular markers that may better define BPH-related pathologies, identify risk of progression of LUTS, and predict response to drug therapy.” 31 Since its establishment, the group has developed a variety of methodologies for acquiring and processing tissue, extracting genetic information, and analyzing potential biomarkers and therapeutic targets. The aforementioned gene expression analysis comparing clinical BPH to histologic BPH identified a novel biomarker JM-27.…”
Section: Biomarkers In Bph: Opportunities For Personalized Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing the importance of targeted therapies for management of BPH, the National Institute of Diabetes and Digestive and Kidney Diseases (NIDDK) established the MTOPS Prostatic Samples Analysis (MPSA) Consortium in 2002 to “identify and validate molecular markers that may better define BPH-related pathologies, identify risk of progression of LUTS, and predict response to drug therapy.” 31 Since its establishment, the group has developed a variety of methodologies for acquiring and processing tissue, extracting genetic information, and analyzing potential biomarkers and therapeutic targets. The aforementioned gene expression analysis comparing clinical BPH to histologic BPH identified a novel biomarker JM-27.…”
Section: Biomarkers In Bph: Opportunities For Personalized Medicinementioning
confidence: 99%
“…Next, a serum-based ELISA assay was developed using an anti-JM-27 monoclonal antibody which could measure serum levels of JM-27 and distinguish between symptomatic and asymptomatic BPH patient sets. 31, 32 Unlike PSA, serum JM-27 levels are not affected by prostate volume, giving JM-27 potential as a biomarker that could be obtained as a diagnostic blood test to risk stratify patients for symptom and disease progression However, additional studies are needed to validate these initial results amongst a larger sample size in order to demonstrate the utility of JM-27.…”
Section: Biomarkers In Bph: Opportunities For Personalized Medicinementioning
confidence: 99%
“…As part of the hallmark Medical Therapy of Prostatic Symptoms (MTOPS) clinical trial, the Prostatic Samples Analysis (MPSA) Consortium attempted to establish and validate potential biomarkers that could stratify the BPH patients according to their response to medical therapy, by using dual antibody sandwich immunoassay of ELISA, which is the most sensitive bioassay technique currently available. 43,44 However, this was an a priori approach targeting specific biomarkers that bypassed the possibility of observing a plethora of low-abundance proteins that might play a significant role on the differential diagnosis between BPH and PCa. Along this theme, the proposed MudPIT approach A, used as a qualitative protein identification tool in this study, can be extended to include relative quantitative features made possible with the use of multiplex stable isotope labeling strategies at the protein or peptide level to further minimize analytical systematic error and to better stratify patients in accordance with prostate pathophysiology analogous to that of the BPH/PCa prostate tissue study reported by the authors.…”
Section: Articlementioning
confidence: 99%
“…In contrast, the Medical Therapy of Prostatic Symptoms (MTOPS) clinical trial, attempted to characterize potential biomarkers that could stratify the BPH patients according to their response to medical therapy, by using the a priori use of the ELISA assay (Mullins et al, 2008). However, such an a priori approach bypassed the possibility in observing unexpected low-abundant tissue specific and secreted proteins that might play a significant role on the differential diagnosis between BPH and PCa.…”
Section: The Quantitative Proteomic Profiling Of Clinical Serum Samplmentioning
confidence: 99%